SIMULASI MONTE CARLO UNTUK ESTIMASI PENGADAAN ATK (STUDI KASUS DI INSTITUT TEKNOLOGI PADANG) - Hamdi Habdillah; Jufriadif Na’am (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2024)
Office Stationery (ATK) is one of the operational needs at the Padang Institute of Technology (ITP). Stationery procurement is carried out twice a year with an annual budget submission. ATK management is carried out manually starting from requests to the transaction system. Current conditions have resulted in procurement planning not being measured, resulting in running out of certain items in the middle of the period or excess of certain items at the end of the year. How to help the procurement department to determine procurement estimates, so that they can provide goods optimally and use the budget more effectively and efficiently for the coming period. Processing is carried out on ATK transaction data using the Monte Carlo simulation method. Simulation stages include determining probability, calculating cumulative distribution, determining intervals of random numbers, forming random numbers and creating simulations. The results of the simulations carried out can determine the estimated quantity of goods procurement and can reduce procurement costs by 25.6% when compared to procurement in the previous even semester period. The level of accuracy of results in predicting future conditions depends on the amount of historical data involved in this process. The simulation method used can be adjusted to the object being studied and the variables that object has.